The People Help the People! Healthcare of the Matico Command in Defense of the Lives of the Shipibo-Konibo Indigenous People During the COVID-19 Pandemic - Giesecke Sara Lafosse, Mercedes Patricia (2024)
We wonder how it was possible for the Matico Command to achieve such a quick and effective response in a context of confusion and fear of death. We propose to understand the way in which Comando Matico managed to manage the pandemic crisis, as an instance of cultural and political affirmation from which they updated ancestral knowledge, through their collective and organized action, in the care of Shipibo-Konibo patients with COVID-19 and comorbidities. Since May 15, 2020, they established a type of strategic indigenous health response, to achieve the acceptance of both, the population served and the DIRESA-U and the GOREU, especially during the first two years of the COVID-19 pandemic. We collected information through interviews with members of the Comando Matico, from its official Facebook page, and from interviews with third parties. We reach the conclusion that its effectiveness was based on the strengthening of its identity, of the indigenous organization, in the communication and dissemination in its mother tongue of its knowledge and practices in traditional health.